HEALTH EDUCATION AS A DOMINANT FACTOR FOR BREAST MILK PROMOTION IN HOSPITAL - Rahmah, Ririn.,RB (2013)
The purpose of this study was to determine the factors that influence breastfeeding newborns at PKU Muhammadiyah Yogyakarta hospital.